The Pathogenesis of Foot-and-Mouth Disease in Pigs - Stenfeldt, Carolina; Diaz-San Segundo, Fayna; de los Santos, Teresa; Rodriguez, Luis L.; Arzt, Jonathan (Frontiers in Veterinary Science, 2016)
The greatest proportion of foot-and-mouth disease (FMD) clinical research has been dedicated to elucidating pathogenesis and enhancing vaccine protection in cattle with less efforts invested in studies specific to pigs. However, accumulated evidence from FMD outbreaks and experimental investigations suggest that critical components of FMD pathogenesis, immunology, and vaccinology cannot be extrapolated from investigations performed in cattle to explain or predict outcomes of infection or vaccination in pigs. Furthermore, it has been shown that failure to account for these differences may have substantial consequences when FMD outbreaks occur in areas with dense pig populations. Recent experimental studies have confirmed some aspects of conventional wisdom by demonstrating that pigs are more susceptible to FMD virus (FMDV) infection via exposure of the upper gastrointestinal tract (oropharynx) than through inhalation of virus. The infection spreads rapidly within groups of pigs that are housed together, although efficiency of transmission may vary depending on virus strain and exposure intensity. Multiple investigations have demonstrated that physical separation of pigs is sufficient to prevent virus transmission under experimental conditions. Detailed pathogenesis studies have recently demonstrated that specialized epithelium within porcine oropharyngeal tonsils constitute the primary infection sites following simulated-natural virus exposure. Furthermore, epithelium of the tonsil of the soft palate supports substantial virus replication during the clinical phase of infection, thus providing large amounts of virus that can be shed into the environment. Due to massive amplification and shedding of virus, acutely infected pigs constitute a considerable source of contagion. FMDV infection results in modulation of several components of the host immune response. The infection is ultimately cleared in association with a strong humoral response and, in contrast to ruminants, there is no subclinical persistence of FMDV in pigs. The aim of this review is to provide an overview of knowledge gained from experimental investigations of FMD pathogenesis, transmission and host response in pigs. Details of the temporo-anatomic progression of infection is discussed in relation to specific pathogenesis events and the likelihood of transmission. Additionally, relevant aspects of the host immune response are discussed within contexts of conventional and novel intervention strategies of vaccination and immunomodulation.